2019
DOI: 10.3233/nre-182468
|View full text |Cite
|
Sign up to set email alerts
|

Improving gait and lower-limb muscle strength in children with cerebral palsy following Selective Percutaneous Myofascial Lengthening and functional physiotherapy

Abstract: BACKGROUND: Selective Percutaneous Myofascial lengthening (SPML) is an innovative minimally invasive surgical procedure, using micro incisions often combined with alcohol nerve block, for managing muscle contractures and stiffness in children with cerebral palsy (CP). There is lack of evidence of effects of a combined intervention of SPML and physiotherapy on gait function and muscle strength in CP. OBJECTIVE: This study investigated the change in gait function and muscle strength in children with CP who under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 30 publications
0
6
0
1
Order By: Relevance
“…Moreover, other studies have shown that lower leg muscle strength may play a critical role in gait [25,26]. In other words, functional decline-represented by the FTSST and GDI findings-may be prevented if gait impairment is ameliorated through exercise therapy and orthopedic treatments to address the aspects of body structure and function in pediatric patients [27][28][29][30], such as strength, balance, or bony abnormalities, particularly in those with GMFCS level I and II spastic cerebral palsy. However, gait quality and physical function in children with cerebral palsy are complex topics that warrant further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, other studies have shown that lower leg muscle strength may play a critical role in gait [25,26]. In other words, functional decline-represented by the FTSST and GDI findings-may be prevented if gait impairment is ameliorated through exercise therapy and orthopedic treatments to address the aspects of body structure and function in pediatric patients [27][28][29][30], such as strength, balance, or bony abnormalities, particularly in those with GMFCS level I and II spastic cerebral palsy. However, gait quality and physical function in children with cerebral palsy are complex topics that warrant further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Most recently, a report including 10 children treated on multiple sites confirmed improvements in gross motor function, muscle strength, and step length. Joint mobility data were collected but not reported [11]. No studies that assess joint excursion after lengthening surgeries were found.…”
Section: Discussionmentioning
confidence: 99%
“…The selective percutaneous myofascial lengthening (SPML) surgical procedure is a minimally invasive method to lengthen contracted musculoskeletal tissues to improve bilateral interactive walking, subsequent functional mobility, and quality of life in children with CP. Developed by RM Nuzzo, SPML differs from other orthopedic surgeries in its aims and procedures [ 11 – 14 ]. Most surgical approaches plan the procedures as a sort of blueprint, with shape and depth, even jigs and patterns used as templates.…”
Section: Introductionmentioning
confidence: 99%
“…CP is one of the most common neurological disorders that is encountered in a healthcare setting. Spastic CP can lead to contractures that can limit the quality of life in patients [6]. These contractures can be released with surgery, and one such surgery is the SPML operation.…”
Section: Discussionmentioning
confidence: 99%